Efeito do mentol e da mentona e sua complementação ao praziquantel no processo inflamatório durante a esquistossomose murina - Feitosa, Karina Alves (Universidade Federal de São Carlos, 2018)
Schistosomiasis is an infectious disease caused by helminths of Schistosoma genus. Around 206 million people worldwide are infected and 200,000 die. In Brazil, only S. mansoni is found and causes mansonic schistosomiasis. The treatment is restricted to only one drug, praziquantel (PZQ), which has been used for 43 years. However, cases of worms with loss of drug sensitivity have been reported and the search for new alternatives that aid in the disease’s treatment are necessary. In this way, the effects of the association of menthol and menthone in defined compositions, 70% and 30% respectively, were evaluated, in addition to its complementation to the PZQ, in inflammation during the chronic’s phase disease. In vitro experiments were performed, evaluating the cytotoxicity of the compounds and the ability to induce the production of nitric oxide (NO) against macrophages (RAW 264.7), in addition to two in vivo experiments independent and distinct. Experiment 1 evaluated menthol + menthone at doses of 70 mg/kg and 100 mg/kg for 15 days and the PZQ-treated group (single dose 400 mg/kg). Treatment started 45 days after infection and euthanasia was performed at 61 days post infection. Experiment 2 evaluated the group treated with menthol + menthone (100 mg/kg) for 13 days, PZQ group (single dose 100 mg/kg) supplemented with 13 days of menthol + menthone (100 mg/kg) and the group treated with PZQ alone (single dose of 100 mg/kg). Treatment started 40 days after infection and euthanasia was performed at 55 days post infection. In the in vitro experiments, there was no cytotoxicity or nitric oxide production. For the experiment 1, the treatment with 100 mg/kg of menthol + menthone promoted the reduction of eggs in the faeces of 14.3%, reduction of 37.8% for adult worms of S. mansoni and 21.7% reduction of hepatic granulomas. Both menthol + menthone treatments significantly reduced the number of blood leukocytes and peritoneal cavity lavage (LPC) and eosinophils. For the IL-4 cytokine, there was a significant reduction in levels in all treated groups compared to the positive control and IL-10, only the group treated with 100 mg/kg of menthol + menthone decreased significantly in relation to the praziquantel group. A lower number of granulomas were observed in the group treated with 100 mg/kg menthol + menthone. The hepatic parenchyma of the groups treated with menthol + menthone were more preserved, in relation to the positive control. For experiment 2, the results obtained to reduce number of eggs (14.3%) and adult worms of S. mansoni (70.8%) were better in the PZQ group supplemented to the compounds. There was a significant reduction in blood eosinophils and LPC only in the groups that had menthol + menthone in their treatment. The results suggest that menthol + menthone in defined compositions, including its complementation to conventional treatment (PZQ), demonstrated antiparasitic properties and above all anti-inflammatory action, thus promoting increased protection of the infected individual against the complications of the chronic phase during mansonic schistosomiasis.
Keywords: Terapêutica; S. mansoni; Anti-inflamatório; Antiparasitário; Mentha x piperita L.; Therapeutics; S. mansoni; Anti-inflammatory; Antiparasitic; Mentha x piperita L; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::IMUNOLOGIA; CIENCIAS BIOLOGICAS::PARASITOLOGIA